Health variables and gill morphology in the tropical fish Astyanax fasciatus from a sewage-contaminated river - Alberto, A.; Camargo, AFM; Verani, JR; Costa, OFT; Fernandes, M. N. (Elsevier B.V., 2005)
The relative condition factor (Kn), gonadosomatic index (GSI), selected hematological variables and gill morphology of the fish Astyanax fasciatus were analyzed in two sites (site I was unpolluted and site 2 was polluted with untreated domestic sewage) of a tropical river (Camanducaia river, São Paulo State, Brazil). The relationship between the body mass (M-B) and the standard length (L-S) of A. fasciatus from both sites was M-B = 0.00799 L-S(3.51843). Tyhe Kn values from both the males and females were significantly higher in site 2. The mean corpuscular hemoglobin and mean corpuscular hemoglobin concentration were higher in females from site 2. Gill tissue anomalies and gill parasites were rare in fish from both sites; however, the number of chloride cells was significantly higher in fish from site 1. A. fasciatus presents high capacity to live in ion-poor and soft water and is able to compensate for environmental changes caused by untreated domestic sewage discharges. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: fish; untreated domestic sewage; condition factor; gonadosomatic index; blood variables; chloride cells; characidae